Acute Kidney Injury and 3-Year Mortality in Elderly Patients After Non-cardiac Surgery - Wu, Qiong-Fang; Xing, Mao-Wei; Hu, Wen-Jun; Su, Xian; Zhang, Dan-Feng; Mu, Dong-Liang; Wang, Dong-Xin (Frontiers in Medicine, 2022)
Objective: Present study aimed to investigate whether acute kidney injury (AKI) was associated with 3-year mortality in elderly patients after non-cardiac surgery. Methods: Present study was a prospective 3-year follow-up study of two randomized controlled trials. A total of 1319 elderly patients who received non-cardiac surgery under general anesthesia were screened. AKI was diagnosed by the elevation of serum creatinine within postoperative 7 days according to KDIGO guideline. The long-term telephone follow-up was performed by investigators who didn’t involve in the two previous trials and had no access to study group assignment. The date of death was recorded according to official medical certification of death. The primary outcome was to investigate the association between AKI and postoperative 3-year mortality by multivariable Cox regression risk model. Results: Totally, 1297 elderly patients (mean age 71.8 ± 7.2 years old) were included. The incidence of AKI was 15.5% (201/1297). In patients with AKI, 85.0% (170/201) of them was at stage 1, 10% (20/201) at stage 2, and 5.0% (11/201) at stage 3. The 3-year all-cause mortality was 28.9% (58/201) in patients with AKI and 24.0% (263/1096) in patients without AKI (hazard ratio 1.247, 95% confidence interval 0.939-1.657, P = 0.128). Multivariable Cox regression showed that AKI was not associated with 3-year mortality after adjustment of confounding factors (adjusted hazard ratio 1.045, 95% confidence interval 0.780-1.401, P = 0.766). Conclusions: AKI was a common postoperative complication, but it was not associated with 3-year mortality in elderly patients undergoing non-cardiac surgery. Interpretation of present result should take the low incidence of severe AKI in consideration which might underestimate the potential association between AKI and mortality.